THE EFFECT OF MENTALIZED-BASED TRETMENT (MBT) ON BODERLINE PERSONALITY DISORDER (BPD) PATIENTS: LITERATURE REVIEW - Ani Nur' Aini (Universitas Airlangga, 2021)
Introduction: Borderline Personality Disorder occurs a lot in line with the development of the technology era and a more practical lifestyle is associated with a personality disorder characterized by poor emotional distress, self-destructive behavior, low quality of life and social problems. Mentalized Based Treatment is one of the therapies used in the treatment of patients with Borderline Personality Disorder. The purpose of this study was to determine the effect of Mentalized Based Treatment on patients with boderline personality disorder.Method: The research method used is a literature review. Search articles using Google Scholar and PUBMED databases. The variables used to search for articles are mentalization-based treatment and borderline personality disorder. The framework used to review is PICOS and inclusion criteria. The articles used are English and Indonesian articles published in 2011 to 2020. The results of the search for articles before the examination are available 117 articles, then 5 articles that match the inclusion criteria will be obtained in reviews. Articles are reviewed and data tabulation is carried.Results: Patients who have done Mentalized Based Treatment can identify the feelings they experience, control their emotions, and are able to interact with other people. The success of therapy is determined by the individual, health facilities, medical personnel, family, and the intensity of therapy.Conclusion: Mentalization-based treatment can be an intervention for Borderline Personality Disorder patients.